1996
DOI: 10.1037/1076-8998.1.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Hostility and hearing protection behavior: The mediating role of personal beliefs and low frustration tolerance.

Abstract: The authors examined whether hostility would negatively be associated with occupational health behavior, namely, the use of hearing protection devices (HPDs). Also examined as possible mediators were the protection motivation theory (PMT) components and low frustration tolerance (LFT). Participants were 226 male industrial workers, all exposed to potentially hearing-damaging noise. Hostility was negatively related to HPD use. It moderately correlated with the PMT components: negatively with perceived susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
2
9
0
2
Order By: Relevance
“…Dissimilar to previous studies of other worker groups, benefits of use (Lusk, Ronis, & Hogan, 1997), and self‐efficacy of use (Lusk, Ronis, & Hogan, 1997; Melamed et al, 1996; Rabinowitz et al, 1996) were not statistically significant predictors of use (i.e., these factors did not separate users from non‐users) in the study reported here. This finding suggests that even in the presence of high scores on the benefits of use and self‐efficacy of use instruments, the presence of high barriers and/or low access and availability may limit the use of hearing protection among farmers.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Dissimilar to previous studies of other worker groups, benefits of use (Lusk, Ronis, & Hogan, 1997), and self‐efficacy of use (Lusk, Ronis, & Hogan, 1997; Melamed et al, 1996; Rabinowitz et al, 1996) were not statistically significant predictors of use (i.e., these factors did not separate users from non‐users) in the study reported here. This finding suggests that even in the presence of high scores on the benefits of use and self‐efficacy of use instruments, the presence of high barriers and/or low access and availability may limit the use of hearing protection among farmers.…”
Section: Discussionsupporting
confidence: 75%
“…Workers who did not perceive barriers (e.g., interference of HPDs with work tasks) reported higher use of HPDs (Lusk, Ronis, & Hogan, 1997; Ronis, Hong, & Lusk, 2006; Wadud, Kreuter, & Clarkson, 1998). A positive relationship was found between HPD use and self‐efficacy (Lusk, Ronis, & Hogan, 1997; Melamed, Rabinowitz, Feiner, Weisberg, & Ribak, 1996; Rabinowitz, Melamed, Feiner, Weisberg, & Ribak, 1996). Lusk, Ronis, and Hogan (1997) also found that, when workers perceived the use of HPDs as having benefits, such as prevention of NIHL and protection of their inner ear, they had higher rates of HPD use.…”
Section: Background and Significancementioning
confidence: 99%
“…After all the variables had been entered into the model, the multiple correlation of this regression was .734, and the adjusted R 2 , considering the overall number of predictors, was .535 (p < .0001), which indicates that the final model included variables that accounted for 53.5% of the variability observed in HPD use. This result is fairly consistent with other authors' findings when exploring multivariable analysis of HPD use, which have varied between 42% and 50% (Lusk et al, 1999;S. Rabinowitz, Melamed, Feiner, & Weisberg, 1996).…”
Section: Use Of Hearing Protection Devices (Hpds)supporting
confidence: 94%
“…Group education is thus the most common training approach in the field. Investigators have shown that instruction, practice, and motivational methods can independently affect the efficiency of a hearing protector (ANSI, 1997;Melamed et al, 1996;Rabinowitz et al, 1996). The amount of instruction impacts greatly on the performance of earplugs and the level of protection afforded by them (Casali & Epps, 1986;Casali & Lam, 1986;Merry et al, 1992).…”
Section: Sumariomentioning
confidence: 97%